LOCAL CULTURE STORIES AS ALTERNATIVE READING MATERIALS FOR STUDENTS (A CONTEXTUAL TEACHING AND LEARNING FOR HIGH AND LOW INTEREST) - Al Amin, Ahmad Fitri (JURNAL SMART, 2017)
This study aims to examine the effectiveness of contextual learning using local culture based stories to improve the skill in reading comprehension especially for narrative texts for students with higher and lower interest in MTs Nahdlatul Muslimin Kudus. The study was conducted using factorial design with two research groups and two control groups. The participants of this study were two classes. The number of subjects was 30 in a class. The data were collected by using a pretest and a posttest. Statistical Package for Social Sciences (SPSS) was used for analyzing the tabulated data. The result shows that there was a significance improvement between pretest and posttest in both control and experimental group with the level of significance 0.000. This means both methods are effective in improving the studentsâ reading skills both for the students with higher and lower interest. The analysis of covariance shows that there was no significant interaction between the contextual learning using local and non-local culture based stories, studentsâ interest, and reading comprehension skills with the level of significance 0.380.